Ruthenium-catalyzed C–H allylation of arenes with allylic amines. Issue 21 (14th May 2018) - Yan, Rui; Wang, Zhong-Xia
Abstract : The Ru-catalyzed pyridyl-directed C–H allylation of arenes with allylic amines was carried out in the presence of 5 mol% of [Ru( p -cymene)Cl2 ]2 and 0.5 equiv. of AgOAc in CF3 CH2 OH. Abstract : The Ru-catalyzed pyridyl-directed C–H allylation of arenes with allylic amines has been developed. This reaction was carried out in the presence of 5 mol% of [Ru( p -cymene)Cl2 ]2 and 0.5 equiv. of AgOAc in CF3 CH2 OH at 75 °C, affording the allylated products of arenes in moderate to excellent yields. The method exhibits a wide scope of allylic amines and arenes and shows a good compatibility of functional groups. The pyrazolyl- and pyrimidyl-directed C–H allylation of arenes was also performed under the same conditions.